First isolation and whole genome characterization of porcine deltacoronavirus from pigs in Peru. Issue 5 (15th March 2022) - More‐Bayona, Juan A.; Ramirez‐Velasquez, Mercy; Hause, Ben; Nelson, Eric; Rivera‐Geronimo, Hermelinda
Abstract: Porcine deltacoronavirus is a newly emergent enteric pathogen affecting swine farms worldwide. It has been detected in several countries in Europe, Asia and North America; yet, it has not been reported in South America. In November 2019, an enteric disease outbreak in a pig farm located in San Martin, Peru, was reported along with submission of three intestinal samples from pigs who succumbed to the disease. Samples were processed for molecular detection by qRT‐PCR, viral isolation and further sequencing analysis. A taqman‐based RT‐PCR was performed to differentiate among the most relevant swine enteric coronaviruses described to date. All samples were positive to porcine deltacoronavirus with a cycle threshold (Ct) value between 9 and 14, revealing a high viral load, while testing negative to porcine epidemic diarrhea and transmissible gastroenteritis viruses. Following detection, viral isolation was performed using PK‐15 and Vero cell lines. After 5 days of inoculation, no cytopathic effect was observed. A second blind passage allowed the observation of cytopathic effect on PK‐15 cells, while it remained absent in Vero cells. A fluorescence test using an anti‐N monoclonal antibody confirmed viral replication. One sample was processed for whole genome sequencing (WGS). In short, raw reads were imported into CLC genomics and assembled de novo. Out of 479k reads generated from the sample, 436k assembled into a 25, 501 bp contig which was 99.5% identical to a reference porcine deltacoronavirus strain from the USA within the North American phylogroup. Yet, there are relevant differences at the nucleotide and amino acid levels compared with previously described porcine deltacoronavirus strains. Altogether, our findings represent the first report of porcine deltacoronavirus in South America, which provides information of its evolutionary origin. Thus, this study offers new insights into the molecular epidemiology of porcine deltacoronavirus infections in the swine industry.